Regional Linkages of Agroforestry Production Value Chain (Case Study in Kon and Ba River Basin) - Huu Xuan, Nguyen; Thinh, Nguyen An (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
This research aims to set a foundation for the establishment of the Ba and Kon river basins’ regional linkages between the Central Highlands and the South Central region according to the value chain of plantation timber and sugarcane. The research uses data collection and statistical analysis methods to establish a database for linking planting, processing, and consumption of plantation timber and sugarcane. The research adopts the Rural Rapid Assessment (RRA) method to assess the efficiency of wood linkages along the value chain of plantation timber goods and uses SWOT analysis to assess strengths, weaknesses, opportunities and challenges for regional linkages of the plantation timber value chain. The research results show that the Ba and Kon river basins have great potentials for the production of sugarcane and plantation timber. In these basins, there have been many models linking along the value chain of goods, linking the stages of production, purchase, transportation, processing, and consumption in order to increase the value of goods. The study has established areas specializing in sugarcane cultivation and concentrated planted forest areas with wood processing factories, and sugar factories in these two river basins. Regional linkages in the basins of the Ba and Kon rivers for the plantation timber and sugar cane value chain are established according to a number of major traffic routes such as national roads 19, 19C, 25 and 29.